The development and implementation of a brief intervention for medically admitted suicide attempt survivors - O’Connor, Stephen S. (Gen Hosp Psychiatry, 2015)
OBJECTIVE: The current study endeavored to establish the feasibility and acceptability of a brief intervention for medically admitted suicide attempt survivors. METHOD: Fifty patients admitted to a Level 1 trauma center were recruited following a suicide attempt. The first 10 patients provided information on what constituted usual care, which in turn informed the creation of the intervention manual and research design. The next 10 patients informed refinement of the intervention and research procedures. The final 30 patients were randomized in a pre-post research design to receive the teachable moment brief intervention plus usual care or usual care only. Patients were assessed prior to randomization and 1 month later by blinded research assistants. Outcomes included patient satisfaction, readiness to change problematic behaviors, reasons for living, and suicidal ideation. RESULTS: Patients rated the brief intervention as “good” to “great” on all items related to client satisfaction. Significant group × time interactions were observed for readiness to change (β=9.02, S.D.=3.73, P=.02) and reasons for living (β=29.60, S.D.=10.22, P=.004), suggesting greater improvement for those patients who received the brief intervention. CONCLUSIONS: Patients admitted to an acute inpatient medical setting may benefit from a brief intervention that complements usual care by focusing specifically on the functional aspects of the suicide attempt in a collaborative, patient-centered manner.